Revision of the Recent species of Exechonella Canu & Bassler in Duvergier, 1924 and Actisecos Canu & Bassler, 1927 (Bryozoa, Cheilostomata): systematics, biogeography and evolutionary trends in skeletal morphology - Cáceres-Chamizo, Julia P.; Sanner, Joann; Tilbrook, Kevin J.; Ostrovsky, Andrew N. (Zootaxa, 2017)
The present study describes species of Exechonella and Actisecos discovered through the examination of recent collections from the Red Sea, coast of Oman and Maldive Islands (Indian Ocean) and the Lizard Island, Australia (Great Barrier Reef, Coral Sea) in comparison with historical collections. Eight species of Exechonella are redescribed: E. grandis (type species), E. ampullacea, E. antillea, E. brasiliensis, E. erinacea, E. pumicosa, E. spinosa and E. verrucosa. Eighteen new species of Exechonella are also described: E. azeezi n. sp., E. catalinae n. sp., E. californiensis n. sp., E. claereboudti n. sp., E. elegantissima n. sp., E. floridiana n. sp., E. harmelini n. sp., E. kleemanni n. sp., E. maldiviensis n. sp. E. nikitai n. sp., E. panamensis n. sp., E. reniporosa n. sp., E. rimopora n. sp., E. safagaensis n. sp., E. similis n. sp., E. variperforata n. sp. E. vavrai n. sp. and E. vieirai n. sp. The species studied were grouped in five species complexes. Additionally, two species from the genus Actisecos—A. regularis and A. discoidea were redescribed. The current revision highlights a number of important taxonomical, biogeographical and morphological questions that are of the general biological interest. Among thеm is a polyphyletic nature of Cheilostomata possessing umbonuloid frontal shield.